Mass Panic Disaster Management in COVID-19 Pandemic - Hamzah Shatri; Edward Faisal; Rudi Putranto (Interna Publishing, 2020)
Coronavirus disease (COVID-19) pandemic occurred abruptly. It is an unexpected disaster. Uncertain treatment for this viral infection increases excessive anxiety, which does not occur only in one person but also in majority of people; therefore, it can create mass panic. Mass panic is a serious problem that must be immediately identified and managed. Mass panic management will reduce COVID-19 incidence.